A case study on the northern Bay of Bengal subsurface thermal structure and ocean mixed layer depth in relation to surface energy exchange processes during Monsoon-77 - RAO, R. R.; GOPALAKRISHNA, V. V.; BABU, S. V. (MAUSAM, 1981)
The short term variability of Mixed Layer Depth (MLD) in relation to the surface energy exchange processes over northern Bay of Bengal is examined using the data collected, during Phase ill of Monsoon- 77. The day-to-day variations of the magnitude of MLD seem to depend on the net heat gain at the surface. Meridional gradient in the Mill in the head of Bay of Bengal due to boundary processes is highlighted. Daily variations in subsurface thermal structure and variability of heat potential are discussed in relation to the genesis of a monsoon depression.